The Implementation of Educational Service Marketing Methods for Islamic Education at MAN 1 OKU Timur - Imron, Imron; Zainal Berlian; Ahmad Zainuri (The Future of Education Journal, 2024)
This study aims to analyze the implementation of educational service marketing methods applied at MAN 1 OKU Timur in enhancing the appeal and image of Islamic education in the community. The research uses a qualitative approach with a case study at MAN 1 OKU Timur. Data were collected through in-depth interviews with the Head of the Madrasah, Siti Mu'arofah, M.Pd.I, as well as other relevant parties, such as teachers and students. The results of the study indicate that the use of educational marketing methods through social media, community-based promotions, and the utilization of religious events plays a significant role in introducing and promoting the values of Islamic education at the madrasah. This study is expected to provide insights for education managers to optimize marketing strategies in improving the school’s image.